The right to stay: Exploring graffiti and street art as political representations against touristification in Lisbon - Fernandes, C.; Batel, S. (Papers on Social Representations, 2023)
Tourism has increased significantly in Southern European cities, with it radically altering central urban neighborhoods and communities’ lives into tourism commodities that often lead to the (in)direct physical and psychological displacement of dwellers. Whereas social sciences’ research has already started to give voice to the psychosocial impacts of this touristification problem, not much attention has yet been paid to how individuals and communities attempt to contest it. Graffiti and street art are forms of political participation that have been traditionally neglected as communicative and citizenship practices by Political and Social Psychology. In this paper, we will contribute to this research agenda by considering graffiti and street art as representational projects, that reflect, propose and negotiate meanings in the public sphere. Through a wandering ethnography, 19 images of ilegal and legal graffiti and street art that directly or indirectly referred to tourism were collected during 2018-2019 in Lisbon historic touristified neighborhoods. The images were then analyzed using Pragmatic Discourse Analysis. Analyses revealed two main themes, on ‘Contesting Touristification’ and ‘Discussing the housing crisis’ and a set of associated subthemes. These reveal that meanings of place as community and as a right, and the relations between touristification, the housing crisis and social justice, are brought to the public space through graffiti and street art by resorting to culturally relevant symbols and associated identities. This research shows graffiti and street art as ways of re-presenting touristification and the housing crisis in Lisbon that contribute to politicizing these issues in Portugal.